2014
DOI: 10.1037/neu0000023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bilingualism on the age of onset and progression of MCI and AD: Evidence from executive function tests.

Abstract: Previous articles have reported that bilingualism is associated with a substantial delay in the onset of both Alzheimer's disease (AD) and Mild Cognitive Impairment (MCI). The present study reports results from 74 MCI patients and 75 AD patients; approximately half of the patients in each group were bilingual. All patients were interviewed to obtain details of their language use, onset of their condition, and lifestyle habits. Patients performed three executive function (EF) tests from the D-KEFS battery (Trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
102
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 65 publications
9
102
1
1
Order By: Relevance
“…The results of this study demonstrated that Cantonese/Mandarin bilingual AD patients were significantly older when AD symptoms began than Cantonese or Mandarin monolingual patients, which is consistent with the previous reports of other language pairs [1-3]. The bilinguals also had an older age than both groups of monolinguals at the first clinic visit.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The results of this study demonstrated that Cantonese/Mandarin bilingual AD patients were significantly older when AD symptoms began than Cantonese or Mandarin monolingual patients, which is consistent with the previous reports of other language pairs [1-3]. The bilinguals also had an older age than both groups of monolinguals at the first clinic visit.…”
Section: Discussionsupporting
confidence: 91%
“…The multivariate linear regression analyses showed that relocation history was not an influential factor associated with the onset age of AD, but the p values reached marginal significance ( p = 0.082), suggesting that relocation history may have the potential to delay the onset of AD. Even though the term “relocation” in this study seems similar to “migration” in the study by Bialystok et al [3], they are substantially different in meaning. Relocation in this study was defined as moving within China.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations